2017
DOI: 10.1111/neup.12366
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of OTUB1 inhibits migration of human glioma cells in vitro

Abstract: OTU domain-containing ubiquitin aldehyde-binding protein 1 (OTUB1) protein, a deubiquitinating enzyme (DUB) which belongs to the ovarian tumor (OTU) family, was reported to be associated with the development of various malignancies. However, the potential function of OTUB1 in human gliomas was still unclear. In this study, we sought to investigate the function of OTUB1 in the pathological process of gliomas and analyze its related clinical significance. Western blot and immunohistochemistry analyses demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…In addition, activation of DCs is accompanied by a migration, however, we observed that DC migration was not dependent on the presence of OTUB1 (Figure ). Another study reported that OTUB1 is a stimulator of migration and invasion in cancer cells . Of note, these cells are derived from different sources and genes involved in the regulation of their migration capacity are distinct from each other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, activation of DCs is accompanied by a migration, however, we observed that DC migration was not dependent on the presence of OTUB1 (Figure ). Another study reported that OTUB1 is a stimulator of migration and invasion in cancer cells . Of note, these cells are derived from different sources and genes involved in the regulation of their migration capacity are distinct from each other.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, these cells are derived from different sources and genes involved in the regulation of their migration capacity are distinct from each other. Silencing of OTUB1 in cancer cells inhibits migration through decreased expression of some extracellular matrix degradation‐related proteins, such as matrix metallopeptidase (MMP)2 and MMP9 and DC migration is under the control of chemokine receptors including C‐C chemokine receptor (CCR)7 and CCR9 and their corresponding ligands CCL19 and CCL21, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the status of OTUB1 in the domain of cancer is becoming more and more important and irreplaceable, for example, OTUB1 was found to up-regulated in colorectal cancer (16), gastric adenocarcinoma (17), esophageal cancer (18), ovarian cancer (19), human glioma (20) and hepatocellular carcinoma (21), and promoted tumor invasion and predicted a poor prognosis. OTUB1 promoted tumor progression mainly via two patterns, the one was to stable the expression of tumorigenesis genes by inhibiting ubiquitination of target protein depending on its deubiquitination function, and another mode didn't depend on its deubiquitination manner (22), by direct interacting with E2 ubiquitin ligase.…”
Section: Introductionmentioning
confidence: 99%
“…Located within locus 11q13.1, ovarian tumor domain-containing ubiquitin aldehyde-binding protein 1 (OTUB1) is expressed in a great range of human tissues, and OTUB1 knockdown in the A549 cells suppressed soft agar colony formation and xenograft tumor growth [12]. Besides, OTUB1 was revealed as a biomarker in the pathogenesis of gliomas and has the potency to be applied as a clinical biomarker for glioma in the future [13]. In this report, the expression pattern of miR-103a in NSCLC patients was surveyed to determine the prognostic values of miR-103a in NSCLC.…”
Section: Introductionmentioning
confidence: 99%